THE GENDER PROBLEMS OF THE INFORMATION MARKET OF IVANO-FRANKIVSK - Копистинська, І. М.; Бойчук, І. В. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article deals with the gender problems of the information market of Ivano-Frankivsk. One number of printed public-political newspaper "Galicia", one number of the public-analytical weekly "Galician correspondent", one site-day of the Internet-edition Kurs.if.ua and one number of the business magazine "City" is taken for analysis. The methodology of the analysis studied the balance of representation of male and female images. The analysis showed that the images of men prevail over women. Also analyzed was local advertising, in which sexist patterns sometimes occur.